2018
DOI: 10.5222/ankem.2018.031
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Antimicrobial Susceptibility Results at a State Hospital in Turkey (2010-2016)

Abstract: ÖZETPseudomonas aeruginosa, nozokomiyal pnömoni, dolaşım sistemi infeksiyonları, üriner infeksiyon ve deri infeksiyonları gibi sağlık hizmetleri gerektiren infeksiyon etkenlerinin önemli bir bölümünü oluşturur. Bu çalışma, yıllara göre P.aeruginosa'nın antimikrobiyal duyarlılığının değişimini belirleyerek antimikrobiyal kullanım politikasının oluşturulmasına yardımcı olmayı amaçlamıştır.Hastanemizde 2010-2016 yılları arasında izole edilen P.aeruginosa suşlarının antimikrobiyal duyarlılıkları, örnek türleri ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In another study published in 2018, Şafak et al reported that amikacin and colistin were the most effective antibiotics in inpatients. 34 Santos et al found colistin resistance of 3.89% in 62 clinical P. aeruginosa isolates. 35 Colistin resistance has come to the fore with the addition of polymyxin group antibiotics to the treatment list, as a result of the development of P. aeruginosa resistance to many other antibiotics in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In another study published in 2018, Şafak et al reported that amikacin and colistin were the most effective antibiotics in inpatients. 34 Santos et al found colistin resistance of 3.89% in 62 clinical P. aeruginosa isolates. 35 Colistin resistance has come to the fore with the addition of polymyxin group antibiotics to the treatment list, as a result of the development of P. aeruginosa resistance to many other antibiotics in recent years.…”
Section: Discussionmentioning
confidence: 99%